Industrial decline and labor reallocation in a transforming economy: Romania in early transition - John S. Earle (IZA Journal of Labor & Development, 2012)
Industrial decline and restructuring in the transition economies presents a prime example of the relationship between changes in aggregate economic indicators and underlying microeconomic adjustments. This paper employs matched labor force survey data to focus on the magnitude and determinants of the labor market flows associated with the fall in industrial employment in Romania from 1993 to 1995. The data show not only a large drop in aggregate industry employment, but also a decline in each of the disaggregated two-digit sectors. Nonetheless, there are substantial gross flows in both directions, again with significant heterogeneity across sectors. Workers leaving jobs in industry have a variety of destinations: jobs in other industrial sectors, in agriculture, and in services, as well as unemployment and non-participation in the labor force; the data show all of these paths to be significant. Multinomial logit estimates indicate that the probability of paths is affected by both individual and firm characteristics. Among other results, university and general high school education tend to raise the probability of job-to-job flows, particularly from industrial jobs to other industrial jobs and to service sectors, but not to agriculture. Workers with primary and vocational education have the highest probability of becoming unemployed and the lowest probability of finding new jobs in services (less than a third the probability for those with university education). Compared with workers in state-owned companies, workers from the private sector, especially from enterprises of mixed ownership have a greater probability of exiting their industry, as well as higher probabilities of finding jobs in services. The largest outflows, however, concern workers from industrial cooperatives, most of whom become unemployed. The data present a mixed picture of social dislocation and improved reallocation.
Keywords: J21; J23; J24; J26; J60; J68; O12; P31; 330; unemployment; sectoral shifts; reallocation; labor force status; labor force surveys; Romania; Fertigungsberufe; Deindustrialisierung; Beschäftigungseffekt; Arbeitsmobilität; Rumänien